DC circuits : contextual variation of student responses - John, Ignatius (Department of Physics, 2016)
Many studies have shown that students (at both school and university) have difficulties in understanding the concepts associated with DC circuits. Two competing theoretical frameworks have been advanced to explain these problems: "misconceptions" and "knowledge-in-pieces". The former is based on the assumption that student ideas are unitary, static and independent of context, while the latter considers student ideas to arise dynamically from flexible combinations of "pieces of knowledge" and that a particular combination of pieces is primed by the context presented. The present work explores the extent to which student responses change as a result of small, fine-grained changes to a simple open circuit with only three components: a battery, a single wire and a resistive element. Three different types of resistive element were used: a light bulb, a heater and a resistor. A previously piloted, eight-question written instrument, consisting of both forced choice responses and free response writing, was administered to two cohorts of non-major, first year physics students from different institutions. The results, consistent across both cohorts, confirmed that context (e.g., type of resistive element used) was critical in triggering student responses. Student reasoning varied widely, and the majority of students used more than one "foothold idea" on which to base their explanations. Only 10% of the combined cohort got all answers (canonically) correct, and all of these students used only the single idea of "loop continuity" as the basis of their explanations. Based on the written responses, and a small number of clarifying interviews, it was clear that sense-making was a key driver in student reasoning. However, either (a) an incorrect explanatory interpretation of a prior experience, or (b) the absence of any experiences from which to extract a key abstract concept, such as "loop continuity", lead to incorrect (canonical) answers. One implication of the findings is that, unlike mechanics, where prior concrete experience is used as the starting point and then refined toward abstract knowledge, it appears that starting with the abstract might be a more effective pedagogical approach. This stands in contrast to many curricula that start with a concrete instantiation such as the light bulb.